Retention of phosphorus in soils receiving bunker silo effluent. (1st December 2022) - Pluer, W.T.; Plach, J.M.; Hassan, A.; Price, D.; Macrae, M.L.
Abstract: The eutrophication of freshwater systems is a pervasive issue in North America and elsewhere, which has been linked to elevated phosphorus (P) loading from watersheds. Most excess P is thought to originate from non-point agricultural sources, and less attention has been given to small rural point sources, such as bunker silos on livestock farms. Sophisticated management practices are rarely used to attenuate nutrients from bunker silo effluent, leaving simple vegetated buffer strips or riparian zones to protect surface water; however, the efficacy of these systems or larger constructed treatment systems is unclear. This study compared two systems receiving bunker silo effluent, one a natural riparian system with a vegetated buffer strip that is the most common practice and the other a constructed treatment system with a forebay, slag filter, and swale. The study quantified P retention within various subsections of each system and characterized the forms of stored P to infer the potential for remobilization. Results indicate that soils receiving bunker silo effluent represent considerable stores of legacy P in the landscape (750 and 3400 kg ha −1 ), the majority of which is stored in labile forms that may be vulnerable to remobilization under the waterlogged conditions that often occur in management practices and riparian zones. Some areas of the systems were able to store considerably more P than others, with the slag filter showing the greatest treatment efficacy. Spatial variability in stored P was apparent, where sections of the systems that directly received effluent retained more P than sections located farther away from bunker silos (indirect inputs). Results indicate that passive treatment systems become P saturated over time, limiting their longterm P removal efficacy. The efficacy of these systems may be improved with the inclusion of sorptive materials as a slag filter within the constructed treatment system significantly increased the life expectancy of that system. Greater understanding of both quantity and forms of P retained in systems and soils receiving bunker silo effluent will help develop management strategies that are more effective and longer-lasting for reducing excess P losses to surface water bodies. Highlights: BMPs stored large quantities of P (750–3400 kg ha −1 ) from bunker silo runoff. Most P was stored in forms vulnerable to remobilization under common conditions. Directly impacted soils retained more P but became P saturated, limiting efficacy. Slag retained the most total P per mass while still being the least P saturated. Spatial analyses of retained P concentrations did not indicate distinct flowpaths.